UWB pulse design method based on approximate prolate spheroidal wave functions - LU Yin; ZHU Hong-bo (Tongxin xuebao)
Coexistence and compatibility was an important issue needed to be considered in ultra-wideband （UWB） impulse radio communications.To avoid interference,one of the effective methods was to design appropriate pulse waveform.UWB pulse design algorithm was established,the approximate solution to the prolate spheroidal wave functions （PSWF） was analyzed,a pulse design method was proposed by using the approximate prolate spheroidal wave functions （APSWF）.The mathematical expression of APSWF was simple and explicit.The simulation shows that pulse based on APSWF meets the power spectral constraint of the FCC’s spectral mask.The APSWF-based pulse waveform can be flexibly adjusted by this method when the spectral mask changes.